Encyclopedia of Life Sciences 2012
DOI: 10.1002/9780470015902.a0002035.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Apomixis

Abstract: Seeds contribute significantly to world food supply. Flowering plants mainly produce seeds by sexual reproduction, which is a driver of genetic diversity. The combination of meiosis during male and female gamete formation, and subsequent gamete fusion at fertilisation in the ovule of the flower to form the embryo compartment of the seed, leads to segregation of parental alleles in seedling progeny. A second fertilisation event generates the endosperm, a nutritive tissue supporting embryo growth and seedling ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Egg cell totipotency is normally suppressed until fertilization (Feng et al, 2013). However, in gametophytic apomixis, diploid egg cells form and can directly develop into zygotes and embryos indicating egg cell totipotency (Koltunow, 2012). It is likely that totipotency of the egg cell is established during the megagametogenesis stage.…”
Section: Totipotency and Somatic Embryogenesismentioning
confidence: 99%
“…Egg cell totipotency is normally suppressed until fertilization (Feng et al, 2013). However, in gametophytic apomixis, diploid egg cells form and can directly develop into zygotes and embryos indicating egg cell totipotency (Koltunow, 2012). It is likely that totipotency of the egg cell is established during the megagametogenesis stage.…”
Section: Totipotency and Somatic Embryogenesismentioning
confidence: 99%
“…Without pollination FS 25, FS 29, FS 89 and FS G118 failed to set fruit, but some other lines set fruits with full seeds (FS A6, FS A13, FS 26, FS 71 and FS 91) (Table 5). It is possible that those full seeds were somatic (adventitious) embryos that were formed in the absence of fertilization (due to the absence of pollination), a rare phenomenon, but also was found in Valencia oranges (Koltunow, 2012). Fei et al (2019) reported that the formation of adventitious embryos was not related to the development of endosperm as a result of fertilization.…”
Section: Fruit and Seed Developmentmentioning
confidence: 99%